ENZYMATIC HYDROLYSIS AND BIOETHANOL PRODUCTION FROM SAMANEA SAMAN USING SIMULTANEOUS SACCHARIFICATION AND FERMENTATION BY SACCHAROMYCES CEREVISIAE AND PICHIA STIPITIS - KUSMIYATI KUSMIYATI; SABDA AJI KURNIAWAN; ABDUL AZIS; TAUFIK ARYADI; HADIYANTO HADIYANTO (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
This study investigated the possibility rain tree pods (Samanea saman) to produce ethanol. The production of ethanol from lignocellulosic material involves four steps, namely: pretreatment, hydrolysis, fermentation, and product separation. The pretreatment and hydrolysis are important steps to improve the production rate and yield of total sugar as well as the reducing sugar. The alkaline and acid pretreatments using H2O2 and H3PO4 were studied at different concentrations (2, 4, 6, 8 %, v / v). From this study, the highest total sugar (18 %) and reducing sugar (9.4 %) contents were generated by 8 % H2O2 pretreatment in compared with those generated by H3PO4. Enzyme loadings (10, 20, 30, 40 FPU·g-1) were studied in hydrolysis step. The effect of enzyme loading show that, the highest total sugar (18 %) and reducing sugar (9.4 %) were obtained at 40 FPU·g-1 cellulase when 8 % H2O2 was used for pretreatment. In fermentation step, two kinds of yeast were used for fermentation (Saccharomyces cerevisiae and Pichia stipitis). Furthermore, the effect of yeast only and the mixture of cellulase and S. cerevisiae yeast were studied. The mixture of cellulase and S. cerevisiae can produce higher ethanol precentage (0.8 %) and (0.46 %) when H2O2 and H3PO4 treatments were used, repectively as compared with mixture of cellulase and Pichia sp. which produced (0.3 %) and (0.12 %) when H2O2 and H3PO4 treatments were used, respectively.